Savings after retirement - Eric French (The University of Western Ontario, Department of Economics, 2022)
Retired households, especially those with high lifetime income, decumulate their wealth very slowly, and many die leaving large estates. The three leading explanations for the "retirement savings puzzle" are the desire to insure against uncertain lifespans and medical expenses, the desire to leave bequests to one's heirs, and the desire to remain in one's own home. We discuss the empirical strategies used to differentiate these motivations, most of which go beyond wealth to exploit additional features of the data. The literature suggests that all the motivations are present, but has yet to reach a consensus about their relative importance.
Keywords: 330; Rentner; Sparen; Vorsichtssparen; Gesundheitskosten; Erbe; Versicherungsschutz; USA